Unsteady stagnation point flow and heat transfer over a stretching or shrinking sheet - Suali, Melini (2012)
The study is focused on investigating the effects of unsteady stagnation point ow and heat transfer over a stretching/shrinking sheet. The problem is modeled as a mathematical formulation that involves a system of partial differential equations. The governing partial differential equations are then transformed into non-linear ordinary differential equations using the similarity transformations. The obtained non-linear ordinary differential equations are solved numerically using the shooting method. For the problem of unsteady stagnation point ow and heat transfer over a stretching/shrinking sheet with prescribed heat ux, the unsteadiness parameter A increases the skin friction f00(0) and the local Nusselt number 1(0). As the values of ratio of stretching/shrinking velocity " and Prandtl number Pr increase,the velocity and temperature profiles increase but the surface temperature decreases. For the problem of unsteady stagnation point ow and heat transfer over a stretching/shrinking sheet with suction/injection, the temperature and velocity profiles increase as the values of f0 increases. As the injection/suction parameter increases the thermal boundary layer thickness increases, thus reduce the heat transfer rate at the surface. For the case of injection, the solutions exist for a certain interval of ", whereas for the suction, there is no such interval appears. For the problem of thermal radiation effects on unsteady stagnation point ow and heat transfer over a stretching/shrinking sheet, the skin friction coefficient f00(0)and the local Nusselt number.